Patterns and Outcome of Traumatic Brain Injury Patients: A Study in a Tertiary Level Military Hospital (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: A traumatic brain injury (TBI) is an injury to the brain caused by an impact to the head. TBI represents a huge global medical and public health problem across all ages and in both civilian and military populations. TBI is characterized by great heterogeneity in terms of etiology, mechanism, pathology, severity and treatment with widely varying outcomes.Objective: To determine the pattern and outcome of traumatic brain injuries in victims reported to emergency and casualty (E&C) department following intensive care with or without surgical intervention.Materials and Methods: This prospective type of observational study was conducted at Neurosurgery department of Combined Military Hospital, Dhaka from October 2013 to March 2017. A total of 675 head injury patients with TBI were assessed with gender, age, cause and type of trauma, GCS on admission, associated other injuries, time lapsed from trauma to hospitalization and care given. The outcome was measured after 72 hours using Glasgow Outcome Scale (GOS).Results: The incidence of TBI was 47.03% among the head injury patients. Common age group was 21-30 years (43.7%) and male victims (66.55%). RTA was the most frequent cause (50.05%) of TBI and the most common pathophysiological cause of TBI was subdural haemorrhage (SDH)(35%) followed by extradural haemorrhage (EDH)(27%). Most patients (45%) had mild TBI. Surgical intervention was required in 45% patients of TBI mainly for the SDH, EDH which had significant positive effect on the TBI patient’s outcome. The majority of patients (77%) had good outcome which included recovery (51.85%) and moderate disability (25.48%). The poor outcome was observed in 23% patients which included death (7.40%), persistent vegetative state (3.11%), severe disability (12.14%) and it was associated with older age, severe TBI (GCS